IFLA President-s Meeting 2015 Istanbul - Zayim, KÜBRA; ZAYİM GEDİK, KÜBRA (My University, 2015)
International Federation of Library Associations and Institutions (IFLA) organizing presidency meetings in connection with the developments for library and information services by the themes defined. Eighth Meeting of Presidency has been organized in cooperation with ANKOS, Turkish Librarians- Association (TLA), Istanbul BilgiUniversity in Istanbul with the invited speakers and attendants from various disciplines. The meeting titled in -The Art of Transformation of Libraries- was carried out in the framework organized under the five major themes. These titles are: